MASP-2 saturation curve in cerebrospinal fluid indicates local synthesis and its equilibrium with soluble and associated forms - Dorta-Contreras, Alberto Juan Juan; González-Losada, Cristobal; Ramos-Robledo, Alejandro; Zerr, Inga; Schmitz, Matthias; Gudmann-Hansen, Annette (Revista Cubana de Investigaciones Biomédicas, 2021)
Introduction: MASP-2 is a mannose blinding lectin associate to serine protease in cerebrospinal fluid and its dynamics through the blood brain barrier is unknown. Objective: To describe MASP-2 diffusion pattern from blood to cerebrospinal fluid. Methods: A transversal observational prospective study was performed 56 control samples of cerebrospinal fluid and serum were employed. ELISA measured MASP-2. Two groups were made: control patients without organic brain disease with normal cerebrospinal fluid and normal barrier function and patients without inflammatory diseases with a blood cerebrospinal fluid barrier dysfunction. Results: MASP-2 concentration in cerebrospinal fluid increase with augment the Q Albumin. QMASP-2 vs. Q Albumin saturation curve indicates that MASP-2 is interacting with other molecules in the subarachnoid environment. The higher inter-individual variation of cerebrospinal fluid MASP-2 of the control compared to the serum MASP-2 indicates that MASP-2 is a protein derived from blood. Conclusions: MASP-2 in CSF is predominantly blood-derived. The saturation curve demonstrates that MASP-2 interacts with the starters of the lectin pathway like mannose binding lectin, ficolins and collectin LK.